2011
DOI: 10.1007/s10900-011-9436-9
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Perceptions of Water Safety and Quality

Abstract: Every day parents make choices about the source of water their families consume. There are many contributing factors which could affect decisions about water consumption including taste, smell, color, safety, cost, and convenience. However, few studies have investigated what parents with young children think about water quality and safety in the US and how this affects the choices they are making. This study aimed to describe the perceptions of parents with regard to water quality and safety and to compare bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 12 publications
2
34
1
2
Order By: Relevance
“…Several studies around the nation have reported a decrease in the quality of drinking water (Hu et al, 2011;Merkel et al, 2012), and the media appears to be addressing water quality issues around the United States as well. Future studies could also evaluate state comparisons, not only noting differences among different states but also different regions in the United States (i.e., rural versus urban, population, etc.).…”
Section: Future Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies around the nation have reported a decrease in the quality of drinking water (Hu et al, 2011;Merkel et al, 2012), and the media appears to be addressing water quality issues around the United States as well. Future studies could also evaluate state comparisons, not only noting differences among different states but also different regions in the United States (i.e., rural versus urban, population, etc.).…”
Section: Future Researchmentioning
confidence: 99%
“…Additionally, areas like Denver, Colorado, have increased public awareness of water issues and water conservation efforts via the media (Stanford, 1996). While residents hold limited trust in popular media, the media still has the ability to raise a level of awareness of water issues (Merkel, Bicking, & Sekhar, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Choosing bottled water over tap water may be related to perceptions of safety, taste, and convenience (213). Understanding water consumption and perceptions of water safety can inform interventions like the Centers for Disease Control and Prevention’s (CDC) Communities Putting Prevention to Work (CPPW), which promotes tap water as a healthful, fluoridated, low-cost, and environmentally friendly alternative (14).…”
Section: Objectivementioning
confidence: 99%
“…Some studies found that community residents in UNGD areas were concerned about the risk of developing cancer (Merkel, Bicking, & Sekhar, 2011), felt that their health was worse than that of residents in neighbouring areas without UNGD (Coons & Walker, 2008), and were more or less likely to support UNGD based on their perception of UNGD as an environmental and public health threat (Kriesky, Goldstein, Zell, & Beach, 2013). While these studies demonstrate that there is a fear of the unknown for many residents, it is not yet clear if some health impacts will manifest, because of latency periods between exposure and effect.…”
Section: Risk Perceptionmentioning
confidence: 99%